The Challenges in Management of Refugees and IDPs in Nigeria - Yunana, Titus Wuyah (Pakistan Social Sciences Review, 2023)
The study examined the challenges in management of refugees and IDPs in Narayi, Kaduna State-Nigeria spanning the period 2015-2021. Descriptive and inferential statistics were used to analyze the quantitative data. Content analysis was also employed to analyze the qualitative data whereas statistical methods, regression and correlation analysis were utilized to analyze the quantitative data. The results of the study however, prove that there exist a significant association between the challenges of refugees and IDPs and their adaptability in Nigeria. According to the result of the regression analysis, lack of education and poor accommodation have a positive influence on adaptability while inadequate food has a negative impact on adaptability of refuges and IDPs in Nigeria for the period of study. The study therefore recommends that governments should enact a local law to compel IDPs management agencies at all levels to stringently observe the UN Guiding Principles on Internal Displacement to the letter. In the alternative, they should adapt these principles as national laws and make them binding on all IDPs management agencies.